Hubungan Manajemen Rekrutmen dan Seleksi Guru Pembimbing Khusus (GPK) terhadap Keberhasilan Pendidikan Inklusi di Sekolah Dasar: - - Utami, Karinta; Nur, Lutfi; Rusmana, Nandang (JPI (Jurnal Pendidikan Inklusi), 2023)
This study aimed to describe the link between the recruitment and selection of Special Guidance Teachers (GPK) and the implementation of inclusive education in primary schools. Ten GPK in SD Labschool UPI Tasikmalaya City were interviewed and given questionnaires. The data was analyzed quantitatively, descriptively, and in terms of correlation. Both variables obtained high scores based on data processing results (management of GPK selection recruitment and implementation of inclusive education). The measured correlation between the two variables is 0.928, showing that the recruiting management carried out on GPK has a significant impact, implying that good recruitment and selection management will support the successful implementation of inclusive education held at SD Labschool UPI Tasikmalaya.Keywords: recruitment and selection, Special Guidance Teacher, Inclusive education, Primary school